FROM INLAND TO OUTLAND: EXPERIENCES OF NON-NATIVE EXPATRIATE TEACHERS TEACHING IN A FOREIGN CONTEXT - Remart Padua Dumlao; Trixia Mengorio (Journal of English Education, 2019)
The numbers of English language learners and limited domestic English language teachers have grown exponentially in Indonesia, Thailand and Vietnam, as well as to the ASEAN region over the past decades due to the demand of globalization. Given the huge cultural and linguistic diversity among learners, educating these populations of English language learners can be a challenging but also beneficial for foreign language teachers. This study aimed to analyse the experiences of fifteen Non-native English Speaking Foreign Teachers (NNESFT) teaching in Indonesia, Thailand and Vietnam. The results of this study suggested that although teachers’ reasons in teaching English language in a foreign classroom were more extrinsic reasons rather that intrinsic and altruistic. NNESFT recognized benefits of teaching in foreign classroom, namely, financial aspects, personal development, and building cultural awareness. Meanwhile, challenges were reported include as a non-native English speaking teachers in a foreign classroom, on the part of textbooks and curriculum, and cultural differences in the classroom. Implications were discussed in light of the findings and recommendations formulated for future research directions.